Sistem Pendukung Keputusan Penempatan Cabang UMKM Berdasarkan Analisis SWOT dengan Metode Promethee - Hondo, Bram Natanfojaen Avore; Novriyenni, Novriyenni; Ambarita, Indah (Yayasan Bina Internusa Mabarindo, 2025)
Increasingly tight business competition encourages Micro, Small, and Medium Enterprises (MSMEs) to have the right strategy in developing their business, one of which is through selecting strategic branch locations. This study aims to design and build a decision support system for MSME branch placement based on SWOT analysis combined with the Promethee method. The case study was conducted on the Cak Kotes MSME, which operates in the beverage sector and has three branches in Binjai City. SWOT analysis was used to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) relevant in location selection. The Promethee method was applied to weight and rank alternative locations objectively and systematically. This web-based system was built using the CodeIgniter framework, the PHP 5.3.7 programming language, and the MySQL database. The results of this system are expected to assist MSME owners in determining the most appropriate branch location for the target market and increase the efficiency and effectiveness of business decision-making.